Pre-desert Tripolita nia: a new archaeological and archaeometrical examination of Red Slip Ware from the Ghirza excavations and the Libyan Valleys Survey - Leitch, Victoria; Bonifay, Michel; Capelli, Claudio; Mattingly, David (Rei Cretariae Romanae Fautorum Acta, 2022)
The First Libyan Pottery Workshop, held in July 2014 in the Society for Libyan Studies archives at the University of Leicester, set out to review the pottery samples from the Ghirza excavations and the Libyan Valleys Survey. A new archaeological and archaeometrical (petrographical) examination of these sherds (some of them previously published by John W. Hayes and John Dore in 1984 and 1996) allowed us to better characterise the Red Slip ware production of the pre-desert region of Tripolitania between the end of the 2nd and the 7th century.